HUKUM KEWARISAN DALAM KOMPILASI HUKUM ISLAM (KHI) DI INDONESIA - Yusuf Somawinata (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2009)
The Islamic laws of inheritance has improved and eliminated the imbalances of the inheritance system conducted by many people both in the past and at present. Islamic laws of inheritance does not contain arbitrariness to the heirs, but gives the absolute justice.The efforts to endorse Islamic laws on the positive laws in Indonesia have been done continuously by the Islamic leaders and prominent figures. These are proven by the emergence of Religious Judicature Competency in article 49 UU No.7 of 1989, and the completing of the joint project between the Supreme Court of RI and the Ministry of Religious Affairs of Indonesia on Islamic Law Compilation containing the material of marital law, inheritance law, and law of religious foundation in 19 91.Since the Presidential Instruction of RI No. 1 of 1991 and the decision of the Ministry of Religious affairs of RI No. 154 of 1991 were issued, Islamic law Compilation in Indonesia had obtained power and juridical form to be practiced by religious court, other administration institutions as well as by community that needs it in solving the problems regulated in this compilation.Inheritance law as regulated in Islamic Law Compilation is basically an inheritance law taken from the opinion of jumhur fuqaha. However, there are some exceptions, I such as in the cases of wasiat wajibah, naqisah (radd), and definition of off spring (walad).